Feminizm postoperaistyczny i filozofia Luce Irigaray – próba uzgodnienia stanowisk - Kujawa, Dawid (Śląskie Studia Polonistyczne, 2019)
In the present article the author endeavours to compare the main assumptions of Italian post-operaist feminism (mostly those related to the Wages for Housework campaign) with Luce Irigaray’s sexuate difference philosophy. Assuming as a departure point the notion of labour force reproduction, the author tries to prove the synergic potential sustaining between the two mentioned perspectives – the most noteworthy convergence between them is the eventually shared ontological horizon stemming from Marx’s perspective on communism as “the real movement which abolishes the present state of things.”